Biocompatible artificial DNA linker that is read through by DNA polymerases and is functional in Escherichia coli - El-Sagheer, Afaf H. (National Academy of Sciences, 2011)
A triazole mimic of a DNA phosphodiester linkage has been produced by templated chemical ligation of oligonucleotides functionalized with 5′-azide and 3′-alkyne. The individual azide and alkyne oligonucleotides were synthesized by standard phosphoramidite methods and assembled using a straightforward ligation procedure. This highly efficient chemical equivalent of enzymatic DNA ligation has been used to assemble a 300-mer from three 100-mer oligonucleotides, demonstrating the total chemical synthesis of very long oligonucleotides. The base sequences of the DNA strands containing this artificial linkage were copied during PCR with high fidelity and a gene containing the triazole linker was functional in Escherichia coli.